Легалізація наркотичних засобів в Україні - Єфремова, А. С. (ХНУРЕ, 2019)
The article provides the reader with some information on advantages and disadvantages of this decision. The text gives valuable information on attitude of residents of the Kharkiv region to this topic. It is especially noted that experience of different countries. It draws our attention to the growing problem of the spread of heavy Chemical drugs.